Studies on the Utilization of Indian Oil Sardine (Sardinella longiceps) for the Preparation of Fish Sausages: 2. Effect of Sodium Bicarbonate Treatment on Meat Characteristics and Sausage Quality - C.N., Ravishankar; T.M.R., Setty; T.S., Shetty (Fishery Technology, 2025)
Studies on the utilization of Indian oil sardine (Sardinella longiceps Valenciennes) for the preparation of minced meat and fish sausages were made. Picked meat was treated with various concentrations of sodium bicarbonate, of which washing the meat with 0.5% was found to be most effective in improving the colour and quality characteristics of the meat and the sausages.